2006
DOI: 10.1021/jp0548927
|View full text |Cite
|
Sign up to set email alerts
|

Reforming of Oxygenates for H2 Production:  Correlating Reactivity of Ethylene Glycol and Ethanol on Pt(111) and Ni/Pt(111) with Surface d-Band Center

Abstract: The dehydrogenation and decarbonylation of ethylene glycol and ethanol were studied using temperature programmed desorption (TPD) on Pt(111) and Ni/Pt(111) bimetallic surfaces, as probe reactions for the reforming of oxygenates for the production of H2 for fuel cells. Ethylene glycol reacted via dehydrogenation to form CO and H2, corresponding to the desired reforming reaction, and via total decomposition to produce C(ad), O(ad), and H2. Ethanol reacted by three reaction pathways, dehydrogenation, decarbonylat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

11
162
2
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 127 publications
(176 citation statements)
references
References 53 publications
11
162
2
1
Order By: Relevance
“…The TPD results obtained for glycerol were similar to previous experiments using ethylene glycol [7] and ethanol. [7] [a] O.…”
supporting
confidence: 88%
See 4 more Smart Citations
“…The TPD results obtained for glycerol were similar to previous experiments using ethylene glycol [7] and ethanol. [7] [a] O.…”
supporting
confidence: 88%
“…The objective of these experiments was to determine whether the chemistry of glycerol is sufficiently similar to that of smaller oxygenates to validate the use of smaller molecules as models in catalysis and surface science studies. We have previously investigated the reactivity of ethylene glycol, [7] ethanol, [7] and methanol [8] on Ni/PtA C H T U N G T R E N N U N G (111) bimetallic surfaces. These studies demonstrated that surfaces with a Ni monolayer on top of PtA C H T U N G T R E N N U N G (111), designated as Ni-Pt-PtA C H T U N G T R E N N U N G (111), display increased reforming activity as compared to either an unmodified PtA C H T U N G T R E N N U N G (111) surface or a PtA C H T U N G T R E N N U N G (111) surface containing a subsurface Ni monolayer, designated as Pt-Ni-PtA C H T U N G T R E N N U N G (111).…”
mentioning
confidence: 99%
See 3 more Smart Citations